Inter-state transfers for cost differences in federations with population mobility and natural resources - Petchey, Jeffrey (Curtin University, 2016)
The Australian system of horizontal scal equalization (HFE) transfers output from low to high cost states. This paper develops a standard model of a federation with an imperfectly mobile population and states which capture economic rents from natural resources and recycle the revenue on the basis of residency. A federal agency, which can be thought of as mimicking the role of the Commonwealth Grants Commission, chooses an inter-state transfer to maximize national social welfare. The contribution of the paper is to show that under the assumptions of the model, the optimal transfer to a state is increasing in its costs, for given costs in other states. This supports the notion of inter-state transfers in favour of high cost states. However, the result does not necessarily validate the magnitude of transfers that we see in practice in the Australian federation.